An Analysis of Students Geometry Skills with Different Visual-Spatial and Logic-Mathematic Intelligence in Solving the Problem of Solid Plane Geometry - Astuti, Desi Puji; Sutopo, Sutopo; Nurhasanah, Farida (Journal of Mathematics and Mathematics Education, 2020)
This paper aims to find out the geometry skills of students with different levels of visual-spatial and logic-mathematic intelligence in solving the problem of solid geometry plane surfaces. It is qualitative descriptive research. Interview and test were employed to get data about students’ geometry skills in solving the problem of solid geometry plane surfaces. To maintain the worthiness of the data, the researcher implemented the time triangulation method. The data analysis comprised of data reduction, data display, and verification. This research used purposive sampling to determine the subjects.  The results of this research indicated that the students with low visual-spatial intelligence and low logic-mathematic intelligence had visual skills level 0, the verbal skills did not reach level 0, the logical skills did not reach level 0, drawing skills of subject RR1 was level 0 and subject RR2 did not reach level 0, and applied skills level 1. The students with low visual-spatial intelligence and high logic-mathematic intelligence had visual skills level 0, verbal skills level 2, logical skills level 1, drawing skills level 1, and applied skills level 1. The students with high visual-spatial intelligence and low logic-mathematic intelligence had visual skills level 0, verbal skills level 2, logical skills level 0, drawing skills level 0, and applied skills level 1. The students with high visual-spatial intelligence and high logic-mathematic intelligence had visual skills level 0, verbal skills level 2, logical skills level 1, drawing skills level 1, and applied skills level 1..